Perancangan Fasilitas Multifungsi untuk Mendukung Aktivitas Manusia dan Anjing - Monica Santoso; Adi Santosa; Grace Setiati Kattu (Intra, 2019)
As time passes, there are many people who chooses to pets in their houses, among them are dogs. For that matter, there are appearances of dog lover communities in many areas, as well as dog cafes in some cities. Without realizing it, there has never been a designer who designs facilities to fulfill the needs of dogs and humans simultaneously in Indonesia. This research is using a design thinking method which starts from understand, observe, point of view, ideate, prototype, test, story telling and business model. The result of this research is one set of multifunctional facilities which includes playing, sitting, and storage facilities for the owner and playing, resting, as well as eating and drinking facilities for dogs. This facility has the modular and knock down feature, which also can be used by dogs and its owner simultaneously.